2014
DOI: 10.1002/cbic.201402339
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Enzyme Conjugates as Chiral Ligands for Sharpless Dihydroxylation of Alkenes in Organic Solvents

Abstract: Conjugates of enzymes and poly(2-methyloxazoline) were used as organosoluble amphiphilic polymer nanocontainers for dissolving osmate, thereby converting the enzymes into organosoluble artificial metalloenzymes. These were shown to catalyze the dihydroxylation of different alkenes with high enantioselectivity. The highest selectivities, found for osmate complexed with laccase polymer-enzyme conjugates (PECs), even exceed those of classical Sharpless catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…The basis of the organo‐soluble osmate‐laccase conjugates is the modification of the enzyme with poly(2‐methyloxazoline) (PMOx) and the subsequent exchange of copper with osmate . As shown previously, these conjugates show excellent enantioselectivity in the dihydroxylation of styrene in chloroform.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The basis of the organo‐soluble osmate‐laccase conjugates is the modification of the enzyme with poly(2‐methyloxazoline) (PMOx) and the subsequent exchange of copper with osmate . As shown previously, these conjugates show excellent enantioselectivity in the dihydroxylation of styrene in chloroform.…”
Section: Resultsmentioning
confidence: 88%
“… Strategy for enzyme modification with PMOx and pyromellitic acid dianhydride and the suggested copper type 1 exchange with osmate by treatment with EDTA according to Ref. .…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, the measured selectivities of the 1:1 complexes of acylated LYS and BSA with osmate are with up to 98 % ee ( S ) comparable to that of other designed AME′s . This shows that simple acylation of readily available proteins and complexation with osmate renders those into enantioselective metalloenzymes for the dihydroxylation of styrene in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Goal of the present study was to explore the potential of poly(2‐ethyloxazoline) (PEtOx) as matrix material for the activation of enzymes in electrospun nanofibers in organic solvents. We choose this polymer, because it was found enzyme friendly in solution, in amphiphilic polymer conetworks based on PEtOx, and even as enzyme–polymer conjugates to make the proteins organosoluble (Konieczny et al, ), reactive (Konieczny et al, ), and even applicable as ligands for organo‐metal catalysis (Konieczny et al, ; Leurs et al, ). Al‐Shehri et al () have reported that enzymes can be electrospun from an aqueous solution of commercial PEtOx ( M w = 500,000 g/mol).…”
Section: Resultsmentioning
confidence: 99%